Activity of a Gel Combination of Aloe Vera (Aloe Vera (L) Burm.F.) and Snail Mucus (Achatina fulica (Ferussac, 1821)) on Burn Wounds in Male White Rats (Rattus norvegicus) Wistar Strains - Artha Yuliana Sianipar; Andre Prayoga; Agrecia Yolanda Nainggolan (Jurusan Farmasi Universitas Negeri Gorontalo, 2023)
Burn injury is produced by thermal stress on the skin tissue. This research aimed to determine the combination of Aloe vera and snail mucus used to treat burns and determine the optimal formula. The research was pure with only a randomized control design, including F1 being given placebo gel, F1 (10%:10%), F2 (10%:15%), F3 (10%:20%), and F4 being given bioplacenton. The gel evaluation and tested for the ability to treat burns on rats for about 21 days. The combination gel made a homogenous formulation with a pH 6 based on pH paper while pH meter results were around 6,27- 6,35 cm, a spread of 5,70-6,60 cm, and a viscosity value of 5.600-7.600 cps that was stable for 3 weeks of storage. This evaluation’s findings are consistent with the provisions of National Standard Indonesia (SNI). The activity optimal combination gel obtained by examining the average diameter and discoloration were 10%:20% (0,5560 cm), 10%:15% (0,8120 cm), 10%:10% (0,9860 cm), bioplacenton (0,4780 cm), and placebo gel (1,5340 cm). On the 21st day, the skin condition of K1, K2, K3, and K4 was normal, however, K0 was not normal. The statistical analysis data is normally distributed (p≥0,05), homogeneous (p≥0,05), and a significant difference in all groups (p0,05). According to the experiment, three gel combination of Aloe vera and snail mucus have an effect on healing burns but 10%:20% (F3) could accelerate the optimal healing process.